Focus group in Information Science: moderator role - Vitoriano, Maria Albeti Vieira (2023)
This paper deals with the role of the moderator in using the focus group for collecting data in academic research. It includes a brief literature review of narrative character about the concept, origin and characteristics of this technique. It shows the skills needed for the practice of the role of moderator and best methods for developing such dynamics of information collection. For the literature review, the articles were accessed through the portals: Coordination for the Improvement of Higher Education Personnel and Google Scholar. It shows the results from the Brazilian Digital Base of Theses and Dissertations; communication and information journals classified as A1, A2 and B1​​; and the annals of the XX National Research Meeting in Information Science, about the use of the focus group in graduate work. It presents postdoctoral work that approaches the role of moderator as a critical success factor in data collection. It concludes that the moderator needs to develop conceptual, procedural and attitudinal skills, of which the latter is the most required. It emphasizes that the researcher can play the role of the moderator or act as a second moderator or an observer and pass this role on to someone with experience in group coordination.